Hysterotomy through Colpotomy for the Management of Fetal Maceration in PGF2α Non-Responsive HF Crossbred Cow - Sreeranjani, Raju; Selvaraju, Mani; Sankar, Palanisamy; Varudharajan, Venkatraman (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Fetal maceration is an uncommon condition where the fetus dies after ossification and undergoes microbial digestion or putrefaction in the uterus till only the mass of bones remains (Dhindsa et al., 2013; Kumar, 2015). Incomplete abortion after the third month of gestation is the main reason for a retained fetal bonymass in the uterus of cows and buffaloes (Sood et al., 2009). Besides, the cow does not display severe systemic illness, but the cow may become slightly febrile, anorexic and depressed with vague signs of intermittent straining, accompanied by a foul, purulent vaginal discharge containing small bones (Newman and Anderson, 2005; Haben, 2020). The retained macerated fetus by administration of luteolytic drug (PGF2α) and fetal bones were removed along with purulent discharges manually (Ramesh et al., 2023). The present case reports the surgical management of PGF2α non-responsive animal affected with fetal maceration by hysterotomy through colpotomy.